2000
DOI: 10.1111/j.1532-5415.2000.tb03867.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical Inactivity and Smoking Increase Risk for Serious Infections in Older Women

Abstract: Modifiable risk factors such as physical inactivity and smoking may place older women at risk for serious infections although the causal link is yet to be explained. Further research in this area may lead to new strategies aimed at reducing the serious burden of infections in the older population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 28 publications
1
9
0
1
Order By: Relevance
“…One large study that included older as well as younger adults demonstrated that the risk of community-acquired pneumonia decreased with increasing physical activity in women (Baik et al 2000). In a separate study, women aged 55 to 80 were followed for a period of 6 years, and physical inactivity was associated with an increased risk of hospitalization due to infection (Leveille et al 2000). Kostka and colleagues (2000) followed adults aged 66–84 for one year to assess both the number of upper respiratory tract infections (URTI) per year and the number of days with URTI.…”
Section: Exercise and Immunosenescencementioning
confidence: 99%
“…One large study that included older as well as younger adults demonstrated that the risk of community-acquired pneumonia decreased with increasing physical activity in women (Baik et al 2000). In a separate study, women aged 55 to 80 were followed for a period of 6 years, and physical inactivity was associated with an increased risk of hospitalization due to infection (Leveille et al 2000). Kostka and colleagues (2000) followed adults aged 66–84 for one year to assess both the number of upper respiratory tract infections (URTI) per year and the number of days with URTI.…”
Section: Exercise and Immunosenescencementioning
confidence: 99%
“…Enhanced T--cell responses may be associated with stronger immunity to control viral and bacterial infections: It has been reported that physically active elderly women have a lower risk of community--acquired pneumonia compared to seden-tary elderly women (Baik et al 2000). On the other hand, a lack of regular exercise is associated with an increased the risk of hospitalization due to infection (Leveille et al 2000). This concept concurs with another study suggesting that physical ac-tivity may increase mucosal immune responses in the elderly, promoting re-sistance to upper respiratory infections (Sakamoto et al 2009).…”
Section: Regular Moderate--intensity Physical Activity Is Associated mentioning
confidence: 99%
“…On the other hand, sedentary habits seem to be associated with increased infection risk in ageing. Leveille et al observed that physical inactivity in women aged 55-80 (followed for a period of 6 years) was associated with an increased risk of hospitalization largely due to infections (88) .…”
Section: Physical Activity Counteracting Age-induced Immunodepressionmentioning
confidence: 99%